A COMPARATIVE STUDY BETWEEN APACHE II AND RANSON’S SCORING SYSTEMS IN PREDICTING THE SEVERITY OF ACUTE PANCREATITIS - kadam, Manohar; Gohil, Dharmendrasinh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aims and objectives of the study are to compare the Ranson’s scoring system with APACHE II score in predicting the severity of acute pancreatitis. Methods: 50 cases having acute pancreatitis were included in this study on the basis of a predefined inclusion and exclusion criteria. Institutional ethical committee was approved the study. The duration of study was 2 years. Informed consent was obtained from the patients. Assessment of severity of pancreatitis was done on the basis of Ranson’s scoring as well as APACHE II score. Final severity score of the patients on the basis of both the scoring systems was assessed to determine the efficacy of each scoring system in predicting the severity. Results: Out of these 50 cases, there were 37 (74%) males and 13 (26%) females. The mean age of affected cases was found to be 36.86±7.91 years. The most common etiological factor was chronic alcoholism which was seen in 22 (44%) patients followed by biliary tract disease or stones (24%), hypertriglyceridemia (14%), post ERCP (2%), idiopathic (14%), and autoimmune pancreatitis (2%). Mild and severe pancreatitis was seen in 35 (70%) and 15 (30%), respectively. APACHE II score was found to be having more sensitivity and positive predictive value for the diagnosis of severe pancreatitis as compared to Ranson’s score. There was no significant difference in specificity, negative predictive value, and accuracy as determined by Ranson’s and APACHE II Score. Conclusion: APACHE II score is better in predicting severity of acute pancreatitis as it is found to have a better sensitivity and positive predictive value for the diagnosis of severe pancreatitis as compared to Ranson’s score.